Bulk X-ray random diffraction patterns using polished thin sections of ordinary chondrites: primordial, thermal, and shock features - Imae, Naoya; Kimura, Makoto; Akira, Yamaguchi; Kojima, Hideyasu (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites / Hayabusa, Wed. 5 Dec. / 2nd floor of the Research/Administration Building at the JAXA Sagamihara Campusat conference object